2016
DOI: 10.1101/064758
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic loci associated with coronary artery disease harbor evidence of selection and antagonistic pleiotropy

Abstract: Traditional genome-wide scans for positive selection have mainly uncovered selective sweeps associated with monogenic traits. While selection on quantitative traits is much more common, very few signals have been detected because of their polygenic nature. We searched for positive selection signals underlying coronary artery disease (CAD) in worldwide populations, using novel approaches to quantify relationships between polygenic selection signals and CAD genetic risk. We identified new candidate adaptive loci… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 205 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…Williams proposed that mutations in pleiotropic genes selected for fitness also increased susceptibility to disease in post-reproductive years, a phenomenon he termed "antagonistic pleiotropy," regarded as the evolutionary origin for senescence in all animals [123,124]. A search for polygenic selection signals underlying coronary artery disease in global populations revealed that such loci are enriched for lifetime reproductive success, supporting the concept of antagonistic pleiotropy [125].…”
Section: Developmental Origins Of Health and Disease (Dohad) (Fig 3)mentioning
confidence: 99%
“…Williams proposed that mutations in pleiotropic genes selected for fitness also increased susceptibility to disease in post-reproductive years, a phenomenon he termed "antagonistic pleiotropy," regarded as the evolutionary origin for senescence in all animals [123,124]. A search for polygenic selection signals underlying coronary artery disease in global populations revealed that such loci are enriched for lifetime reproductive success, supporting the concept of antagonistic pleiotropy [125].…”
Section: Developmental Origins Of Health and Disease (Dohad) (Fig 3)mentioning
confidence: 99%